DIVERSITY OF ECTOPARASITES ON BATS IN DRAMAGA, BOGOR, INDONESIA - Virgilius Martin Kelake Kedang; Yanri Rizky Natanael Simangunsong; Susi Soviana; Upik Kesumawati Hadi; Supriyono (BIOTROPIA, 2023)
Ectoparasites infestation is one of the major health problems affecting animals, including bats, which are known as reservoir hosts for various pathogens. Several reports have shown that a comprehensive understanding of ectoparasites on these animals is crucial from a public health perspective. Therefore, this study aims to identify the diversity of ectoparasites on bats in Dramaga, Bogor, Indonesia. The samples were captured at night with a mist net and then identified using the species identification key. Ectoparasites were collected from the body of the samples and identified using a microscope. A total of 56 bats from 9 species, namely Cynopterus brachyotis, Cynopterus sphinx, Cynopterus titthaecheilus, Macroglossus sobrinus, Rousettus leschenaultii, Myotis muricola, Nycteris javanica, Pipistrellus javanicus, and Scotophilus kuhlii were obtained in this study. The results of ectoparasites identification showed the presence of Basilia spp., Eucampsipoda sp., Leptocyclopodia ferrarii (Nycteribiidae), Raymondia sp. (Streblidae), Meristaspis spp., Spinturnix spp. (Spinturnicidae), and ticks (Ixodidae). The total prevalence of infested bats was 51.7%, with females tending to have a higher intensity compared to males. Bats species with the highest prevalence of infestation were Rousettus leschenaultii and Myotis muricola. Meanwhile, this study found no ectoparasites on Macroglossus sobrinus and Scotophilus kuhlii.